An exploratory study of service quality effectiveness on intention to complain among mobile phone users in Kuching - Tan, Mei Fong (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study aims to investigate the relationship between customer service effectiveness and complaint behavior. This study focuses on users of mobile telecommunication services through a questionnaire survey in Kuching. 224 respondents participated in this study. Methodologies employed are descriptive, exploratory factor analysis, Pearson correlation and multiple regression analysis. The findings of this study show that complaint behavior is significantly influenced by reliability as paramount in service quality effectiveness. The findings of this study also shown control variables such as gender and monthly income have significant relationship with complaint behavior. Theoretically, this study contributes to the existing literature by providing insights on the relationship between service effectiveness and complaint behavior in the mobile telecommunication industry. For managers, findings of this study provide better understanding and a further insight on service quality effectiveness in influencing consumers’ complaint behavior. Limitations of this study include methodology employed and sample size. Recommendations for future study suggest extending to investigate other service industries, investigate other factors that could affect customer complaint behavior, conduct a nation-wide study and adopt a larger sample size.